1994
DOI: 10.1159/000236690
|View full text |Cite
|
Sign up to set email alerts
|

Serum Tryptase and Urinary 1-Methylhistamine as Parameters for Monitoring Oral Food Challenges in Children

Abstract: To study the usefulness of urinary 1-methylhistamine and serum tryptase concentration as monitoring parameters in clinical settings, we investigated 32 children with atopic dermatitis and suspected food allergy during oral food challenges with eggs and cow’s milk. Urinary 1-methylhistamine (MH) excretion increased significantly within lh after positive oral food challenges (p < 0.006), but showed considerable variation in negative challenges. MH seems to be a sensitive parameter (92.8%), but its specifity is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
2
11
0
2
Order By: Relevance
“…Some investigators have reported significant increases in urinary 1-methylhistamine levels 1 hour after a positive OFC result, as well as a significant increase in serum tryptase levels, but the sensitivity of these parameters is low. 90 Similar results were observed by Ohtsuka et al 91 when measuring plasma tryptase and histamine levels up to 4 hours after a positive challenge result but were not confirmed by others for eosinophil cationic protein level in the blood and tryptase levels in the blood or saliva. 92 …”
Section: Assessment Of Blood Parameterssupporting
confidence: 75%
“…Some investigators have reported significant increases in urinary 1-methylhistamine levels 1 hour after a positive OFC result, as well as a significant increase in serum tryptase levels, but the sensitivity of these parameters is low. 90 Similar results were observed by Ohtsuka et al 91 when measuring plasma tryptase and histamine levels up to 4 hours after a positive challenge result but were not confirmed by others for eosinophil cationic protein level in the blood and tryptase levels in the blood or saliva. 92 …”
Section: Assessment Of Blood Parameterssupporting
confidence: 75%
“…In addition, in patients with positive oral food challenges, an increase in serum tryptase (mast-cell-specific mediator) [31], plasma histamine [32] and urinary 1-methylhistamine [31] was also observed in the first hours, suggesting that eosinophils, basophils and mast cells react early. The ongoing reaction seems to be triggered and controlled by lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In our patients with food allergy, diagnosed by allergological and standardised challenge procedures [15,19,20], gastrointestinal manifestation are predominant. The most characteristic finding was a significant reduction of the intensity of abdominal pain during a hypoallergenic diet consisting of potato and rice.…”
Section: Discussionmentioning
confidence: 80%
“…During the first two days, patients consumed a normal, unrestricted diet. This was followed by a two day period with an elimination diet consisting exclusively of potatoes and rice [20,21]. Food intake was allowed until 2 p.m., but no later to avoid interference of histamine containing foods (such as fish or cheese) [22].…”
Section: Collection Of Urine and Plasmamentioning
confidence: 99%